Convertible Party Clothing Design "Lumora" and Fashion Product Quality Analysis - Diah Ayu Listiawati; Sri Endah Wahyuningsih (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
The issue of sustainable fashion has encouraged the development of fashion products that are not only oriented toward aesthetics, but also toward efficiency of use and product sustainability. One relevant design approach in this context is transformative or convertible fashion. This study aims to describe the design process and analyze the quality of “Lumora” convertible partywear, a garment that offers more than one visual appearance within a single product while maintaining the essential characteristics of party attire. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Product quality was assessed through validation tests conducted by expert panelists and trained panelists, based on several indicators, including design, aesthetics, sewing and finishing techniques, overall appearance performance, and product uniqueness. The results indicate that the “Lumora” convertible party dress falls into the very feasible category. The novelty of this research lies in the development of convertible partywear as a sustainable fashion solution through improved efficiency of use, supported by a systematic analysis of product quality. The findings suggest that convertible fashion designs have strong potential to support sustainable fashion practices by reducing the need for ownership of multiple party garments.